Combined intensive blood pressure and glycemic control does not produce an additive benefit on microvascular outcomes in type 2 diabetic patients - Ismail-Beigi, Faramarz (Kidney Int, 2011)
A reduction of either blood pressure or glycemia decreases some microvascular complications of type 2 diabetes, and we studied here their combined effects. In total, 4733 older adults with established type 2 diabetes and hypertension were randomly assigned to intensive (systolic blood pressure less than 120mmHg) or standard (systolic blood pressure less than 140mmHg) blood pressure control, and separately to intensive (HbA1c less than 0.060) or standard (HbA1c 0.070–0.079) glycemic control. Prespecified microvascular outcomes were a composite of renal failure and retinopathy and nine single outcomes. Proportional hazard regression models were used without correction for type I error due to multiple tests. During a mean follow-up of 4.7 years, the primary outcome occurred in 11.4% of intensive and 10.9% of standard blood pressure patients (hazard ratio 1.08), and in 11.1% of intensive and 11.2% of standard glycemia control patients. Intensive blood pressure control only reduced the incidence of microalbuminuria (hazard ratio 0.84), and intensive glycemic control reduced the incidence of macroalbuminuria and a few other microvascular outcomes. There was no interaction between blood pressure and glycemic control, and neither treatment prevented renal failure. Thus, in older patients with established type 2 diabetes and hypertension, intensive blood pressure control improved only 1 of 10 prespecified microvascular outcomes. None of the outcomes were significantly reduced by simultaneous intensive treatment of glycemia and blood pressure, signifying the lack of an additional beneficial effect from combined treatment.